The roles of translation activities in learning financial and banking terminology in the book “English for finance and banking” by assoc. Prof. Dr. Nguyen Xuan Thom to felte students majoring in translation = vai trò của hoạt động dịch trong việc học thuật ngữ tài chính ngân hàng đối với sinh viên biên phiên dịch trong cuốn sách “Tiếng anh tài chính ngân hàng” của pgs.ts. Nguyễn Xuân Thơm - Đỗ, Thị Ngoan (ĐHQGHN - Trường Đại học Ngoại Ngữ, 2021)
The purpose of the present study was to investigate the efficiency of translation activities in the acquisition of financial and banking terms in the “English for Finance and Banking” course. Next, it attempted to provide recommendations for better integrating translation activities into the course. This study was based on a brief theoretical literature overview, analysis of the results from the survey questionnaires and the translation test. The findings of the survey suggested that translation was an effective tool for students’ acquisition of financial and banking terms in the “English for Finance and Banking” course in the Faculty of English Language Teacher Education, ULIS, VNU.